Pacaran dan Perilaku Seksual Remaja Di Provinsi Sulawesi utara (Analisis Data Survei RPJMN Remaja Tahun 2013) - Wijayanti, Urip Tri (JURNAL ILMIAH SOCIETY, 2015)
One of the survey elaborated on teenager dating behavior is youth RPJMN. Respondents in this survey are unmarried teenager on the range age between 15-24 years old who are selected in the family’s survey. Analyses are needed in order to make this survey being useful. The data resources used in this analysis are the results from 2013 RPJMN. The results stated 95% had handrails, 63% had kissed, and 24% had touched/stimulate their couple’s body. All of these percentages are above the national average. Furthermore, for the teenager percentages who had sexual intercourse both man and women are also above the national standard. In details, 13 % man teenager and 7 % women teenager had sexual intercourse. Based on those survey, there are some suggestions, firstly, the attendance of PIK R/M on schools or universities must be more active. It is necessary to socializing the genre with proactive system from BKKBN coordinate with the Department of Education. The may come to the schools coupled with utilizing counseling teachers who have been trained by BKKBN. The existence of religious leaders, community and traditional leaders who have been trained in the KKB program and PK BKKBN program should be empowered, because they are figures whose close to the people (teenagers and parents). Keywords: Dating behavior, RPJMN youth